2011
DOI: 10.1021/co200072z
|View full text |Cite
|
Sign up to set email alerts
|

Novel Application of α-Azido Aldehydes in Multicomponent Reactions: Synthesis of Triazolo-Fused Dihydrooxazinones via a Passerini Reaction–Dipolar Cycloaddition Strategy

Abstract: α-Azido aldehydes can be employed in Passerini reactions with isocyanides and various propiolic acids to afford the three-component adducts in moderate to good yields. These compounds undergo a straightforward azide-alkyne dipolar cycloaddition to furnish triazolo-fused dihydrooxazinones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…13 C NMR (100 MHz, CDCl 3 ) d 136. 3,129.1,128.8,127.3,68.0,. Light yellow oil, 82.9 mg, 73% yield, 1 H NMR (400 MHz, CDCl 3 ) d 7.…”
Section: General Procedures For the Synthesis Of 2a-2kmentioning
confidence: 99%
See 1 more Smart Citation
“…13 C NMR (100 MHz, CDCl 3 ) d 136. 3,129.1,128.8,127.3,68.0,. Light yellow oil, 82.9 mg, 73% yield, 1 H NMR (400 MHz, CDCl 3 ) d 7.…”
Section: General Procedures For the Synthesis Of 2a-2kmentioning
confidence: 99%
“…Introduction 1,2-Azido alcohols are versatile precursors in organic synthesis for a wide variety of target compounds such as triazoles, 1 triazole-fused dihydrooxazinones, 2 2-oxazolidinones, 3 1,4-oxazepines and 1,3-oxazines, 4 oxazaborolidines, 5 and 1,3-oxazolidines. 6 More importantly, they have been widely employed for the regioselective preparation of 1,2-amino alcohols and highly oxygenated compounds such as carbohydrates and nucleosides.…”
mentioning
confidence: 99%
“…In addition, the catalyst can be reused at least seven times without significant loss of activity. De Moliner et al [260] reported the synthesis of novel series of triazolo-fused oxazinones 270, in a two step procedure. The synthesis occurs through a MW-assisted Passerini cycloaddition process.…”
Section: Scheme 48 Mw-assisted Ugi 4-component Reaction Leading To Pmentioning
confidence: 99%
“…Further post-modification has been showcased by the MW-assisted CuI catalyzed intramolecular amidation within 3,4-dihydro-3-oxo-2H-1,4-benzoxazines 276 affording an original heterocyclic scaffold 277 (Scheme 63). De Moliner et al [260] reported the synthesis of novel series of triazolo-fused oxazinones 270, in a two step procedure. The synthesis occurs through a MW-assisted Passerini cycloaddition process.…”
Section: Scheme 48 Mw-assisted Ugi 4-component Reaction Leading To Pmentioning
confidence: 99%
“…Yields of 1,2,3-triazole based on the azidoalcohols are 62-70%. [28] Similar syntheses using U-4CRs instead of the P-3CR of before have also been performed. [29] Not a MCR, but a highly efficient Cu(I)-isocyanide complex has been developed as a heterogeneous catalyst for azide alkyne cycloaddition in water [30] to improve click chemistry.…”
Section: Microwave Assisted Synthesis Of Three Nitrogen Atoms Containmentioning
confidence: 99%